CALCULATION AND AN EXPERIMENTAL RESEARCH PARAMETERS OF SAMPLES OF A FERROMAGNETIC MATERIAL - A.P. POPOV; M.R. VINOKUROV (Advanced Engineering Research, 2009)
In present clause the decision of a linear problem of calculation of an electromagnetic field in system a conductor on which the sine wave current covered with a ferromagnetic conducting pipe proceeds is resulted. The resulted analytical researches are confirmed with experimental data which results allow with a sufficient degree of accuracy to define the characteristic of ferromagnetic conducting environments.